From Nonfunctioning Adrenocortical Cancer to Biochemically Silent Paraganglioma Associated with SDHB Mutation: An Uncommon Presentation of a Patient with a Retroperitoneal Mass - Izabella Freitas; Anna Albuquerque; Luiz de Marco; null Eduardo; José Renan Melo; Juliana Drummond; Beatriz Rocha (Case Reports in Endocrinology)
The combination of clinical characteristics and diagnostic exams including imaging, laboratory, and molecular tests help in the differential diagnosis of retroperitoneal lesions. We report a 41-year-old male with a metastatic retroperitoneal lesion with atypical characteristics, displaying pathological findings consistent with both nonsecretory pheochromocytomas/paragangliomas and adrenal cortex carcinoma. The patient was examined for abdominal pain, weight loss, and hypertension. Abdominal computed tomography showed a 21 × 8 × 10-cm right retroperitoneal mass. He was initially diagnosed as pheochromocytoma/paraganglioma (PHEO/PGL). However, the diagnosis was later changed to adrenocortical carcinoma based on histopathological features of the metastatic lesions and the findings of normal urinary levels of catecholamines/metanephrines. Systemic chemotherapy and abdominal radiotherapy were performed, in addition to multiple surgical resections, with no satisfactory response. The indolent course of the disease and minimal impact on the patient’s performance status led to a genetic evaluation which resulted in the identification of a germline mutation in the succinate dehydrogenase complex subunit B (SDHB). An immunohistology review of previous slides was consistent with the hypothesis of a neuroendocrine tumor. Forty percent of the patients with PHEO/PGL have an underlying germline mutation. SDHB mutation is frequently associated with metastatic disease and dominant secretion of noradrenaline and/or dopamine. In addition to the metastatic disease, few cases with the mutations can be a biochemically silent PHEO/PGL. We concluded that the patient presented a metastatic abdominal paraganglioma associated with an SDHB mutation and we reinforced the need to perform genetic screening for all adrenal/extra-adrenal lesions characteristic of PHEO/PGL.